Emigracija Poljakov v Veliko Britanijo po vstopu Poljske v Evropsko unijo - Balažič, Gregor (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Emigration of Poles to Great Britain after Poland's entry into the European union. The text deals with the case of emigration of Poles to Great Britain. The common economic market and free movement of the labour has its effects in working migrations. The reason lies in perceptible economic differences and development and social standard disparities between old and new members of EU.The purpose of the text is to highlight the effects and consequences of emigration on society and space in both countries. At the forefront is a personal view of emigrants and their experiences that found their (temporary) home in Great Britain due to their wish to earn money. The theoretical part is methodologicaly based on already published scientific findings on the topic of migrations. The main part presents some problems of emigration of Poles to Great Britain and explain them with the analysis of individual contributions published on the world wide web because this kind of researches are still occuring due to the case time vicinity. The conclusion emphasises the future problems of emigration to EU. There are expectations that the aims of migration policy in the future will be oriented in adapting to the circumstances of economically and developmentally differentiated and even more globalised EU.
Keywords: imigranti; Poland; Poljska; emigracija; Velika Britanija; European Union; Evropska unija; ekonomske migracije